Phylotyping and Determining the Antimicrobial Susceptibility of Cutibacterium acnes Isolated from Patients with Acne Vulgaris - ÜLGER, NURVER (ANKARA MICROBIOLOGY SOC, 2021)
Cutibacterium acnes (formerly known as Propionibacterium acnes), obligate anaerobic gram-positive diphtheroid, is a member of normal skin microbiota and frequently isolated from acne lesions and also in various infections as an opportunist pathogen. Within the last decade, distinct phylogroups of C.acnes have been discovered, and specific strains associated with human disease were defined. Increasing resistance to antimicrobials used in the treatment of C.acnes infections has been reported. Resistance rates vary among isolates from different geographic locations. However, knowledge about the antimicrobial susceptibility patterns of C.acnes is limited in Turkey. Determining the phylotypes of C.acnes isolates and providing antimicrobial susceptibility data will be very useful in understanding the pathogenesis of the disease, preventing the development of resistance, and applying rational and effective empirical treatment. The aim of this study was to determine the phylotypes and antimicrobial susceptibility patterns of C.acnes and to investigate the relationship among C.acnes phylotypes, the severity of acne and the antimicrobial resistance. C.acnes isolates cultivated from the acne lesions of 57 patients who admitted to the dermatology outpatient clinic of our university hospital and from the skin of 62 healthy control group in a six-month period were included in the study. The acne lesions on the face and chest/upper back were given a score according to the Global acne grading system (GAGS) for describing the severity of acne. The severity was graded as mild if the score was 1-18, moderate with scores from 19 to 30, severe with scores from 31 to 38, and as very severe if the score is more than 39. The isolates were identified by using matrix assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). Phylotype analysis was performed by polymerase chain reaction (PCR) using specific primers. The minimum inhibitory concentrations (MICs) of clindamycin, erythromycin, azithromycin, tetracycline and doxycycline were determined by agar dilution technique recommended by Clinical and Laboratory Standards Institute (CLSI) for anaerobic bacteria. The majority of the isolates (patient; n=47, control; n=47) in both of the patient and control groups were phylotype IA, followed by type IB and type II, respectively and no type III C.acnes was detected. There was no correlation between acne severity and bacterial phylotypes. The resistance rates of clindamycin, erythromycin, azithromycin, tetracycline and doxycycline were found to be 22.8%, 29.8%, 35.2%, 3.5% and 5.3% in the acne patients group, respectively, whereas in the control group the incidence of resistance to these antimicrobials was 11.3%, 21%, 38.7%, 1.6% and 1.6%, respectively. There was no significant difference in antimicrobial resistance between the patient and control groups, except erythromycin (p=0.043, Fisher's exact) as well as no relationship was found between antimicrobial resistance and phylotypes in both of the groups. The number of isolates, resistant to two or more antimicrobials, was higher in the patients with acne. C.acnes isolates were highly resistant to clindamycin, erythromycin and azithromycin. Type IA constituted the majority of the phylotypes. There was no significant relationship between C.acnes phylotype, antimicrobial resistance and acne severity.
Keywords: Cutibacterium acnes acne vulgaris; phylotype; antimicrobial susceptibility; GAGS score; POLYMERASE-CHAIN-REACTION; PROPIONIBACTERIUM-ACNES; ANTIBIOTIC SUSCEPTIBILITY; RESISTANCE; STRAINS; SURVEILLANCE; LESIONS